(untitled) (Al-Academy, 2024)
The aesthetics of hybridization in contemporary painting and its reflection on the productions of art education students are an important subject in the field of painting at theoretical and practical levels in academic study, whether theoretical or practical. Al-Iraqi is one of the arts with historical roots and a distinguished position among other artistic genres. Painting has received a sufficient level of development through the use of various contemporary aesthetics to advance it for the better. The methodological framework included the problem of research and the need for it, and then the importance of research came in shedding light on the aesthetics of contemporary Iraqi painting, and the impact of these aesthetics on the productions of students of art education and the benefit that was reflected in their official productions. The research aimed to reveal immediate aesthetics and their mechanisms, and the extent of their reflection on the productions of art education students. By stopping and defining terms? The theoretical framework included two sections: the first: a historical introduction to contemporary Iraqi painting, its roots and beginnings. The second: contemporary Iraqi painting aesthetics. The research procedures included: The research community and the research sample included (3) official works, The results and conclusions reached by the two researchers: The aesthetics appeared strongly in all the art education students’ outputs in all samples. The student relied on his imagination to produce new formal compositions. 3. The small number of textbooks on drawing aesthetics to be taught to students of the Department of Art Education